A Case Study of the Implementation of the English Teaching in ABBS Surakarta - Pamungkas, Damar Jati; Hikmat, Mauly Halwat (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to evaluate the efficacy of an immersive English teaching program, with a special emphasis on Indonesian educational establishments. It also aims to evaluate how the curriculum affects students' conversational fluency and self-assurance in speaking English while highlighting obstacles to their academic language proficiency, particularly in areas with technical terminology. Methodology: Document analysis, semi-structured interviews, and classroom observations were used to gather data using a qualitative research approach. The multifaceted data collection procedure made this full understanding of the program's effectiveness and the learning environment possible. Results: The data show that the program effectively raises students' confidence and conversational fluency in English, mostly through consistent exposure and a nurturing learning environment. However, there are still obstacles to achieving academic language proficiency, especially in fields like science and math, where pupils find it difficult to understand technical terms. Applications/Originality/Value: To help students better support themselves in understanding complicated academic subjects in English, the study finds that teachers need specialized professional development. Enhancing the program's focus on academic language and giving teachers specialized training are two suggestions for improvement. The curriculum can better balance academic and conversational language development by focusing on these areas, ensuring that students achieve in both. The results add to our understanding of immersive language instruction and provide guidance for improving comparable initiatives in order to improve student performance.